Effects of performance-based financing on availability, quality, and use of family planning services in the Democratic Republic of Congo: an impact evaluation - Drouard, Salomé; Brenner, Stephan; Antwisi, Delphin; Toure, Ndeye Khady; Madhavan, Supriya; Fink, Guenther; Shapira, Gil (Studies in family planning, 2024)
Access to high-quality family planning services remains limited in many low- and middle-income countries, resulting in a high burden of unintended pregnancies and adverse health outcomes. We used data from a large randomized controlled trial in the Democratic Republic of Congo to test whether performance-based financing (PBF) can increase the availability, quality, and use of family planning services. Starting at the end of 2016, 30 health zones were randomly assigned to a PBF program, in which health facilities received financing conditional on the quantity and quality of offered services. Twenty-eight health zones were assigned to a control group in which health facilities received unconditional financing of a similar magnitude. Follow-up data collection took place in 2021-2022 and included 346 health facility assessments, 476 direct clinical observations of family planning consultations, and 9,585 household surveys. Findings from multivariable regression models show that the PBF program had strong positive impacts on the availability and quality of family planning services. Specifically, the program increased the likelihood that health facilities offered any family planning services by 20 percentage points and increased the likelihood that health facilities had contraceptive pills, injectables, and implants available by 23, 24, and 20 percentage points, respectively. The program also improved the process quality of family planning consultations by 0.59 standard deviations. Despite these improvements, and in addition to reductions in service fees, the program had a modest impact on contraceptive use, increasing the modern method use among sexually active women of reproductive age by 4 percentage points (equivalent to a 37 percent increase), with no significant impact on adolescent contraceptive use. These results suggest that although PBF can be an effective approach for improving the supply of family planning services, complementary demand-side interventions are likely needed in a setting with very low baseline utilization.
Gesehen am 06.08.2024
Online veröffentlicht: 16. April 2024